Strengthening the environmental dimensions of the sustainable development goals in Asia and the Pacific stocktake of national responses to sustainable development goals 12, 14, and 15. (Asian Development Bank, 2019)
This report presents the results of a survey of 15 developing countries in Asia and the Pacific regarding Sustainable Development Goals (SDGs) 12, 14, and 15.It also looks at selected environment related targets that have a direct relationship with responsible consumption and production, and sustainable marine and terrestrial ecosystems management. The report was completed under the first phase of a technical assistance project by ADB, with the aim of understanding and helping its developing member countries address the issues and challenges behind effective integration of these SDGs into national policies, plans, and programs.